Relationship Between Religiosity And Controversial Products And Offensive Nature Of Advertising Appeals - Mohammad Noorizzuddin Nooh; Syadiyah Abdul Shukor; Muhammad Ridhwan Ab. Aziz; Khairil Faizal Khairi; Mahdhir Abdullah (International Journal of Arts and Commerce, 2024)
Journal of Marketing Management, Vol. 2(2), June 2014